Estado nutricional de los habitantes de 11 a 18 años del Centro Curva de Sun – distrito de Moche, empleando medidas antropométricas durante los meses marzo – abril 2008. - Rodríguez Isla, Karla Elcira (2009)
In order to know the nutritional status of adolescents in the populated center of Curva Sun of Moche district, we were realized an Anthropometric assessment of 82 adolescents, the adolescents were weight, height, and took his ages in realized years. The low of weight for height was 40.24%, which means that they have acute malnutrition. The indicator height for age recorded a deficit of 45.12%, meaning of chronic malnutrition. Male adolescents had a higher percentage of obesity than women, but they had lower percentage of chronic-acute malnutrition, and only one male adolescent had a chronic malnutrition and obesity at a time